Acute prenatal exposure to ethanol on gestational day 12 elicits opposing deficits in social behaviors and anxiety-like behaviors in Sprague Dawley rats - Diaz, Marvin R. (Behav Brain Res, 2016)
Our previous research has shown that in Long Evans rats acute prenatal exposure to a high dose of ethanol on gestational day (G) 12 produces social deficits in male offspring and elicits substantial decreases in social preference relative to controls, in late adolescents and adults regardless of sex. In order to generalize the observed detrimental effects of ethanol exposure on G12, pregnant female Sprague Dawley rats were exposed to ethanol or saline and their offspring were assessed in a modified social interaction (SI) test as early adolescents, late adolescents, or young adults. Anxiety-like behavior was also assessed in adults using the elevated plus maze (EPM) or the light/dark box (LDB) test. Age- and sex-dependent social alterations were evident in ethanol-exposed animals. Ethanol-exposed males showed deficits in social investigation at all ages and age-dependent alterations in social preference. Play fighting was not affected in males. In contrast, ethanol-exposed early adolescent females showed no changes in social interactions, whereas older females demonstrated social deficits and social indifference. In adulthood, anxiety-like behavior was decreased in males and females prenatally exposed to ethanol in the EPM, but not the LDB. These findings suggest that social alterations associated with acute exposure to ethanol on G12 are not strain-specific, although they are more pronounced in Long Evans males and Sprague Dawley females. Furthermore, given that anxiety-like behaviors were attenuated in a test-specific manner, this study indicates that early ethanol exposure can have differential effects on different forms of anxiety.